COVID-19: Challenges associated with the treatment of Head and Neck Oncology and Laryngology Patients in the COVID-19 era (2020)
This review explores the changes to practice associated with COVID-19 for providers treating patients with head and neck cancer and laryngeal pathology. The aim of the review is to highlight some of the challenges and considerations associated with treating this patient population during the pandemic. Additionally, it seeks to discuss some of the areas of concern related to ramping up clinical volume.